KOMUNIKASI PERSUASIF KOMUNITAS 1000_GURU RIAU PADA KEGIATAN TRAVELING AND TEACHING UNTUK MENINGKATKAN SADAR PENDIDIKAN DI DAERAH PEDALAMAN RIAU - Admiraldy Eka Saputra; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Understanding of education according to the National Education Law no. 20 in 2003, is a learning process in such a way so that learners can develop their potentials actively in order to have self-control, intelligence, skills in social, religious spiritual strength, personality and character mulia.Upaya conducted by the Community 1000_Guru mem persuasif Riau with the local community inland to care about education through activities Traveling and Teaching.This study aims to determine the credibility of a communicator, messages and media used by this community to improve education in rural areas aware of Riau.This research uses descriptive qualitative research methods. Informants consisted of two people who are the management teams 1000_Guru Community Riau and two volunteers who've participated in the traveling and teaching by using purposive and two people who are teachers who teach in schools in remote areas using technique. accidental sampling Data collected by means of participant observation, interview and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed that Komunitas1000_Guru Riau has credibility as a communicator who can provide motivation on the importance of education to children in remote areas. Riau 1000_Guru Community persuasive message that is using verbal messages include clarity, candor, and the precision and nonverbal messages. The media used is the first community media offline,using props and film about education. Second, the social network used Twitter and Instagram.Third, the print media that work together to cover the activities Traveling and Teaching is a Tribune Pekanbaru.Keywords: persuasive communication 1000_guru community Riau inactivities traveling and teaching to improve awareness of education in rural areas in Riau